Reviving an old idea: can artificial pneumothorax play a role in the modern management of tuberculosis? - Motus, I Y; Skorniakov, S N; Sokolov, V A; Egorov, E A; Kildyusheva, E I; Savel'ev, A V; Zaletaeva, G E (The international journal of tuberculosis and lung disease, 2006)
To determine the usefulness of artificial pneumothorax (AP) in the management of pulmonary tuberculosis (PTB) patients when anti-tuberculosis treatment is ineffective. We evaluated the outcome of therapy in 214 patients with cavitary PTB bacteriologically confirmed by culture treated during 1998-2004, 78.9% of whom had multidrug resistance. AP was applied in 109 patients (56 newly diagnosed TB and 53 retreatment cases). A control group consisted of 105 patients (respectively 55 and 50) treated without AP. The average period of AP application was 4.5 months for newly diagnosed patients and 9 months in retreatment cases. Anti-tuberculosis treatment regimens in both groups were based on drug susceptibility test results. Culture negativity was achieved in patients treated with AP in all new cases and in 81.1% of retreatment cases. Cavity closure occurred in 94.6% and 67.9% respectively. In the control group, culture negativity was achieved in respectively 70.9% and 40.0%, and cavity closure occurred in respectively 56.3% and 24.0%. AP considerably improved the treatment outcome in both newly diagnosed and retreatment patients. This procedure can be considered a useful addition in managing certain patients with cavitary TB, particularly those with drug resistance.